Isolated dwarfism and sexual dimorphism in a mainland population of the greater short-horned lizard (Phrynosoma hernandesi) and the Great Plains toad (Anaxyrus cognatus) - Megan E. Lahti; Leigh C. Latta, IV; Michael E. Pfrender; Edmund D. Brodie (PLoS ONE, 2025)
Body size is an important biological concept as it impacts nearly all aspects of an organism. In mainland systems, body size tends to show clinal variation; however, drastic body size shifts are typically limited to insular systems in correspondence with abrupt changes in climate patterns and resource availability, often in coordination with reduced genetic diversity. We investigate a rare occurrence of dwarfism and its influence on sexual size dimorphism (SSD) among two mainland species inhabiting the San Luis Valley (Valley) using museum and live specimens. The Valley population of the greater short-horned lizard ( Phrynosoma hernandesi ) is 33.7% smaller and the Valley population of the Great Plains toad ( Anaxyrus cognatus ) is 32.9% smaller than populations surrounding the Valley (Outside). The greater short-horned lizard exhibits female-biased SSD range wide, and female-biased SSD among Valley populations is maintained for head length and width but is inconsistent among test groups for radius, hand, and femur length. In the Great Plains toad, SSD is absent among museum specimens from the Outside population and live specimens the Valley population, but shows a weak presence in parotoid gland morphology among museum specimens from the Valley. Although the mechanisms underlying dwarfism and possible selective pressures associated with shifts in female-biased SSD are unknown, we present a rare instance of mainland dwarfism and its influence on SSD.